Morphodynamics and Stratigraphic Architecture of Shelf-Edge Deltas Subject to Constant vs. Dynamic Environmental Forcings: A Laboratory Study - Straub, Kyle M. (Frontiers in Earth Science, 2019)
When deltas dock at continental margins they construct thick stratigraphic intervals and activate continental slope sediment routing systems (SRS). Given their thickness, these deposits have the capacity to store detailed paleo-environmental records. Several competing theories describe how SRS comprised of linked deltas-continental slopes respond to sea level cycles of varying magnitude and periodicity. I explore this in a physical experiment where the topography of a coupled delta-slope system was monitored at high resolution. This allows development of process-based theory for the response of SRS to external forcings at the land-ocean interface. Connection between these environments was promoted with input conditions that generated plunging hyperpycnal flows at river mouths. The experiment had three stages, which included: 1) a delta-slope system aggrading with no sea level cycles, 2) a system responding to low magnitude and high frequency sea level cycles, and 3) a system responding to a high magnitude and long period cycle. All stages shared an identical background pseudo-subsidence rate. Here the magnitudes and periods of sea level cycles are discussed relative to key autogenic scales. I find that, on average, sediment transport to the marine is promoted during lowstand conditions in all stages. However, the scale of the sea level cycles with respect to emergent autogenic scales controls the predictability of this response, with greater stochasticity and thus lower predictability for the response to smaller and shorter sea level cycles. Analysis of two SRS suggests that predictable responses can require sea level cycle amplitudes greater than 50 m and periods longer than 200 kyrs, but will vary with system size.